Different WC particle size reinforced FeCoNiCrMn high-entropy alloy coating and preparation method thereof
By reasonably controlling the mass fraction and particle size of WC particles in FeCoNiCrMn high-entropy alloy coating, and using ball mill mixing and laser cladding technology, the poor strengthening effect caused by insufficient or excessive addition of WC particles in high-entropy alloys is solved. , realizes coating preparation with high strength, high hardness and high wear resistance.
Patent Information
- Application Number
- CN202411451851.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
AI Technical Summary
The number of WC particles added to high-entropy alloys is too small or the particle size is too small, resulting in the diffusion strengthening effect not obvious; while too many additions or the particle size are too large, it will cause the material to be brittle and it is difficult to achieve reasonable strength improvement.
By reasonably controlling the mass fraction and particle size of WC particles in the FeCoNiCrMn high entropy alloy coating, the mass fraction of WC particles is set to 15%, the particle size is controlled between 20μm~55μm or 100μm~150μm, and the ball mill mixing is used. and laser cladding process steps to ensure uniform mixing and good bonding of WC particles and high entropy alloys.
The strength, hardness and wear resistance of high-entropy alloy coatings have been greatly improved, while avoiding the brittleness of the material and significantly improving the overall performance of the coating.
Smart Images

Figure CN119457053A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser additive manufacturing, and in particular to a FeCoNiCrMn high-entropy alloy coating reinforced with different WC grain sizes and a preparation method thereof. Background Art
[0002] High entropy alloys are composed of 5 or more elements, and the atomic fraction of each main element is between 5wt% and 35wt%. High entropy alloy coatings have excellent comprehensive properties such as toughness, wear resistance, and corrosion resistance. Its appearance breaks the traditional alloy system and proposes a new direction for alloy design. There are many high entropy alloy systems, among which the system with Fe, Co, Ni, and Cr as the core occupies an important part in the research of high entropy alloys. The elements have low mixing entropy, and each element has a single FCC or BCC structure, which makes it easier for alloys prepared by these elements to form FCC or BCC solid solution structures, resulting in excellent mechanical properties in all aspects. Since high entropy alloys contain a large amount of precious materials, if all high entropy alloys are used, the production cost will be very expensive. Therefore, depositing high entropy alloys on the surface of the workpiece can effectively extend the service life of the workpiece and reduce production costs. Laser cladding is an advanced surface enhancement process with fast processing speed, small heat-affected zone, small deformation, and obvious metal connection. Therefore, studying the laser cladding layer of high entropy alloy films is a very effective means.
[0003] High entropy alloy coatings can achieve the effect of surface modification. Usually some important parts will use this alloy, such as aerospace, nuclear energy, etc. Since these parts work in relatively harsh environments, high entropy alloy coatings need to have certain hardness, toughness, wear resistance and corrosion resistance and other good properties. In recent years, people have been improving the properties of high entropy alloy coatings by adding elements and other methods. Researchers have found that the properties of the coating can be improved by adding WC particles, which has a significant effect. The study found that by adding WC particles, the dispersion strengthening effect is exerted to inhibit dislocation movement. Under the premise of ensuring that the plasticity and toughness remain basically unchanged, the strength and hardness of the material are effectively improved. The strength of the high entropy alloy coating has been improved, its internal structure is more uniform, the number of pores and cracks is reduced, and the overall performance has been improved.
[0004] However, if the number of WC particles added to the high-entropy alloy is too small or the particle size is too small, the dispersion strengthening effect will not be obvious. If the number of WC particles added is too large or the particle size is too large, the material will become brittle. Therefore, it is crucial to reasonably control the mass fraction and particle size of the added WC particles to improve the strength of the high-entropy alloy coating. Summary of the invention
[0005] In view of the above problems, the present invention provides a FeCoNiCrMn high-entropy alloy coating reinforced with different WC particle sizes, and improves the strength of the high-entropy alloy coating by reasonably controlling the mass fraction and particle size of the high-entropy alloy coating in the high-entropy alloy coating. At the same time, the present invention provides a method for preparing the high-entropy alloy coating, and powder feeding is performed simultaneously to make the fusion of different components more uniform, thereby making the grains of the microstructure uniform.
[0006] Technical solution: The first aspect of the present invention provides a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes. The alloy coating is composed of FeCoNiCrMn high entropy alloy powder and WC particles, the mass fraction of the FeCoNiCrMn high entropy alloy powder is 85%, the mass fraction of the WC particles is 15%, and the particle size of the WC particles is 20μm~55μm or 100μm~150μm.
[0007] Preferably, the molar fractions of the elements in the FeCoNiCrMn high entropy alloy powder are: the molar fraction of Fe is 18-22%, the molar fraction of Co is 18-22%, the molar fraction of Ni is 18-22%, the molar fraction of Cr is 18-22%, and the molar fraction of Mn is 18-22%.
[0008] Preferably, the particle size of the WC particles is 20 μm to 55 μm.
[0009] The second aspect of the present invention provides a method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes, which specifically comprises the following steps: Step 1, ball-milling the FeCoNiCrMn high entropy alloy powder and the WC particles to obtain a mixed powder; Step 2: Put the mixed powder into a beaker and place it in a drying oven for drying; Step 3, pre-treating the substrate surface; Step 4: The powder is passed through a synchronous powder feeding laser cladding device to obtain a WC particle reinforced FeCoNiCrMn high entropy alloy coating.
[0010] Preferably, in step 1, the mass percentage of the ball-milled mixed ceramic balls and the FeCoNiCrMn high entropy alloy powder is 1:1, the rotation speed of the ball mill is 200-500 rpm, and the mixing time of the mixed powder is 12-24 h.
[0011] Preferably, in step 2, the operating temperature of the drying oven is 120-150° C., and the time is 8-12 hours.
[0012] Preferably, in step 3, the substrate is pretreated by first grinding off the oxide film on the surface of the alloy with sandpaper, then spraying the surface with sandblasting to remove oil stains, then cleaning with alcohol, and finally drying with a hair dryer.
[0013] Preferably, in step 4, the laser cladding process parameters for preparing the composite coating are: laser power of 1200W~1800 W, scanning speed of 600mm / min~720 mm / min, spot diameter of 6 mm, powder feeding amount of 0.6g / min~10g / min, defocusing amount of 36 mm, and coating overlap rate of 45%.
[0014] Preferably, in step 4, the layer thickness of the high entropy alloy coating is 0.4-0.8 mm.
[0015] Preferably, the particle size of the FeCoNiCrMn high entropy alloy powder is 45-105 μm.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention enhances the FeCoNiCrMn high entropy alloy coating phase by controlling the size and mass fraction of WC particles, so that the complementary performance of WC particles and high entropy alloy is compatible and synergistic, and the hardness, wear resistance, modulus and other properties of ordinary high entropy alloy coating are superior, thereby realizing the preparation of coating with high strength, high wear resistance and corrosion resistance.
[0017] 2. The composite powder composed of Cr, Mn, WC and other elements has a simple FCC structure, so it has high toughness, high strength and high strength. By introducing refined WC particles into the matrix, it can effectively inhibit the movement of dislocations and effectively inhibit grain growth, further improving the toughness of the material.
[0018] 3. The present invention also provides a method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes, and simultaneously feeding powder makes the fusion of different components more uniform, thereby making the grains of the microstructure uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The scanning electron microscope morphology and particle size diagram of the spherical composite powder in the embodiment of the present invention (where a1, b1, and c1 are scanning electron microscope morphology diagrams of FeCoNiCrMn powder, larger particle size (20μm~55μm) WC particles, and smaller particle size (20μm~55μm) WC particles, respectively; a2, b2, and c2 are particle size diagrams of FeCoNiCrMn powder, larger particle size (100μm~150μm) WC particles, and smaller particle size (20μm~55μm) WC particles, respectively); Figure 2XRD patterns of the WC / HEA composite coating of Examples 1-2 of the present invention and the HEA coating of the comparative example (the left side is the 20°-100° XRD pattern, and the right side is the 43°-44° XRD pattern); Figure 3 The microstructure diagrams of different parts of the WC / HEA composite coating of Examples 1-2 of the present invention and the HEA coating of the comparative example (where a, b, and c represent the FeCoNiCrMn coating, the large-size WC, and the small-size WC, respectively; 1, 2, and 3 represent the upper, middle, and lower parts of the coating, respectively); Figure 4 EDS line scans of the WC / HEA composite coatings of Examples 1-2 of the present invention and the HEA coatings of the comparative example (a is the comparative example; b is Example 1; c is Example 2); Figure 5 The EDS line scan image of the undissolved WC powder of the WC / HEA composite coating of Examples 1-2 of the present invention (where a is Example 1; b is Example 2); Figure 6 1 is a microhardness distribution diagram of the WC / HEA composite coating of Examples 1-2 of the present invention and the HEA coating of the comparative example; Figure 7 The friction coefficient and wear rate diagrams of the WC / HEA composite coatings of Examples 1-2 of the present invention and the HEA coating of the comparative example (a friction coefficient diagram; b wear rate diagram); Figure 8 The wear morphology diagrams of the WC / HEA composite coatings of Examples 1-2 of the present invention and the HEA coating of the comparative example (a is the comparative example; b is Example 1; c is Example 2); Fig. 9 X3D wear tracks and two-dimensional cross-sectional wear tracks of the WC / HEA composite coatings of Examples 1-2 of the present invention and the HEA coating of the comparative example (a is the comparative example, b is Example 1, c is Example 2, and d is the two-dimensional cross-sectional wear track); Fig.10 Polarization curves of the WC / HEA composite coating of Examples 1-2 of the present invention and the HEA coating of the comparative example in 3.5% sodium chloride solution; Fig.11 The corrosion morphology of the WC / HEA composite coating of Examples 1-2 of the present invention and the HEA coating of the comparative example (a is the comparative example; b is Example 1; c is Example 2); Fig.12 The surface residual stress of the WC / HEA composite coating of Examples 1-2 of the present invention and the HEA coating of the comparative example; Fig.13 This is a process flow chart of WC / HEA of Example 1-2 of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Embodiment 1: A FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes, the alloy coating consisting of FeCoNiCrMn high entropy alloy powder and WC particles, the mass fraction of the FeCoNiCrMn high entropy alloy powder is 85%, the mass fraction of the WC particles is 15%, and the particle size of the WC particles is 100 μm to 150 μm; Furthermore, the molar fractions of the elements in the FeCoNiCrMn high entropy alloy powder are: the molar fraction of Fe is 18-22%, the molar fraction of Co is 18-22%, the molar fraction of Ni is 18-22%, the molar fraction of Cr is 18-22%, and the molar fraction of Mn is 18-22%.
[0022] Coating preparation: Powder mixing: High entropy alloy powder and WC powder with a particle size of 100 μm~150 μm in corresponding molar ratio are weighed and mixed and put into a ball mill. The mixed powder is stirred at 300 rpm for 24 hours using a ball mill to mix them thoroughly.
[0023] Powder drying: Put the mixed powder into a beaker and place it in a drying oven at 150°C for 12 hours under vacuum.
[0024] Substrate pretreatment: First use sandpaper to remove the oxide film on the surface of the alloy, then use sandblasting to spray the surface to remove oil stains, then clean it with alcohol, and finally blow it dry with a hair dryer.
[0025] Laser cladding: The RC-HSLC-6000 ultra-high-speed cladding equipment of Nanjing Zhongke Yuchen Co., Ltd. in China was selected, which was equipped with the RFL-C6000 laser device (maximum power 6000W) of Wuhan Raycus Fiber Laser Technology Co., Ltd. The nozzle uses coaxial four-way powder feeding, and both the powder feeding gas and the protective gas are argon. The laser cladding process parameters are: laser power of 1800 W, scanning speed of 720 mm / min, spot diameter of 6 mm, powder feeding amount of 10 g / min, defocusing amount of 36 mm, and coating overlap rate of 45%.
[0026] Example 2: A FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes, wherein the alloy coating is composed of FeCoNiCrMn high entropy alloy powder and WC particles, the mass fraction of the FeCoNiCrMn high entropy alloy powder is 85%, the mass fraction of the WC particles is 15%, and the particle size of the WC particles is 20μm~55μm.
[0027] Furthermore, the molar fractions of the elements in the FeCoNiCrMn high entropy alloy powder are: the molar fraction of Fe is 18-22%, the molar fraction of Co is 18-22%, the molar fraction of Ni is 18-22%, the molar fraction of Cr is 18-22%, and the molar fraction of Mn is 18-22%.
[0028] Coating preparation: Powder mixing: High entropy alloy powder and WC powder with a particle size of 20 μm to 55 μm are weighed and mixed in a corresponding molar ratio and placed in a ball mill. The mixed powders are stirred at 300 rpm for 24 hours using a ball mill to mix them evenly.
[0029] Powder drying: Put the mixed powder into a beaker and place it in a drying oven at 150°C for 12 hours under vacuum.
[0030] Substrate pretreatment: First use sandpaper to remove the oxide film on the surface of the alloy, then use sandblasting to spray the surface to remove oil stains, then clean it with alcohol, and finally blow it dry with a hair dryer.
[0031] Laser cladding: The RC-HSLC-6000 ultra-high-speed cladding equipment of Nanjing Zhongke Yuchen Co., Ltd. in China was selected, which was equipped with the RFL-C6000 laser device (maximum power 6000W) of Wuhan Raycus Fiber Laser Technology Co., Ltd. The nozzle uses coaxial four-way powder feeding, and both the powder feeding gas and the protective gas are argon. The laser cladding process parameters are: laser power of 1800 W, scanning speed of 720 mm / min, spot diameter of 6 mm, powder feeding amount of 10 g / min, defocusing amount of 36 mm, and coating overlap rate of 45%.
[0032] In the tests of Examples 1-2 and the comparative example, the comparative example selected a FeCoNiCrMn high entropy alloy powder without adding WC particles, wherein the molar fraction of Fe was 18-22%, the molar fraction of Co was 18-22%, the molar fraction of Ni was 18-22%, the molar fraction of Cr was 18-22%, and the molar fraction of Mn was 18-22%; the coating preparation process was the same as that of Examples 1-2, omitting the powder mixing step.
[0033] Table 1: Molar ratio of elements in FeCoNiCrMn high entropy alloy powders in Examples 1-2 and Comparative Examples Table 2: Molar ratio of elements in high entropy alloy (HEA) powder in Examples 1-2 and Comparative Examples Microstructure characterization: The coating was cut into 10mm×10mm×10mm samples, and then ground and polished with sandpaper. The sample surface was corroded with a special high-entropy alloy corrosion solution for 60 seconds. The microstructure of the coating was analyzed using an optical microscope (Olympus BX53M), an ultra-depth electron microscope (Olympus DSX1000), a scanning electron microscope (CIQTEKSEM3100) and an energy spectrometer (Oxford Xplore15). The internal phase composition of the coating was analyzed by an X-ray diffractometer (Rigaku UltimaIV).
[0034] Mechanical properties test: The microhardness of the coating was tested using a Vickers microhardness tester (HVS-1000), with the load set to 9.8N and the holding time to 15 seconds. During the test, the hardness test of the coating was measured along the deposition direction and perpendicular to the deposition direction. In the direction perpendicular to the deposition, a position was measured every 0.2mm, and each position was measured 5 times, and the average value was taken as the hardness value of the point; the friction and wear test was carried out using a reciprocating friction and wear tester (MMF-10000N). Before the experiment, the coating surface was ground with sandpaper, cleaned in an ultrasonic cleaner and then blown dry. Before the test, the sample was weighed 5 times, and then the friction and wear test was carried out. The test conditions were set as follows: load 200N, time 30 minutes, amplitude 5mm, frequency 1Hz, sliding speed 10mm / s. After the test, the sample was cleaned again with an ultrasonic cleaner and the weight of the sample was measured. The coating wear rate was calculated by formula 1, and the surface morphology of the coating after wear was observed using SEM. The electrochemical corrosion test was performed using an electrochemical workstation (CHI760E). Before the test, the coating was cut into samples of 10mm×10mm×3mm and ground. The sample was then wrapped with epoxy resin, leaving an area of 0.36mm². The corrosive medium was 3.5% NaCl solution. After the test, the corroded surface was cleaned with alcohol, and the corrosion morphology was observed using SEM after drying.
[0035] Figure 2The XRD spectra of FeCoNiCrMn high entropy alloy coating and coating with WC particles of different particle sizes are shown in Figure (a). The high entropy alloy coating presents a single FCC phase, with diffraction peaks at 43.5°, 50.6°, 74.5° and 90.4°, and the corresponding peak surface indices are (111), (200), (220) and (311), respectively. This shows that high entropy alloys tend to form a simple solid solution structure. After adding WC particles, the coating phase composition is FCC phase and M5C phase. This is because the WC particles decompose under the action of laser, and C atoms combine with high entropy alloy atoms to form M5C phase. As the WC particle size decreases, the M5C phase content increases, because small-sized WC is easier to decompose under the action of laser, which increases the M5C phase content in the coating. As can be seen from Figure (b), after adding WC particles, the diffraction peak of the FCC phase moves to the small angle direction, indicating that the lattice constant decreases. This is due to the solid solution of W atoms into the FCC matrix phase, resulting in lattice distortion. The addition of small-sized WC particles makes the diffraction peak shift to smaller angles more obviously, indicating that more W atoms are dissolved into the matrix phase, further increasing the degree of lattice distortion.
[0036] Figure 3 Figure 1 shows the microstructure of high entropy alloy coatings with different WC particle sizes. Figure a shows the microstructure of the coating without WC particles, and Figures b and c show the microstructure of the coating with WC particles of different particle sizes. It can be seen that a black boundary is formed at the junction of the coating and the substrate, and there are no defects such as cracks and pores, indicating that a good metallurgical bond is achieved between the coating and the substrate. The microstructure of the coating is planar crystals, cellular crystals, columnar crystals and equiaxed crystals from bottom to top. Compared with the coating without WC particles, the coating with WC particles has a more refined structure, and the addition of small-size WC particles significantly improves the refinement of the coating structure. It can be seen from the figure that there are incompletely dissolved WC particles inside the coating. During the solidification process of the coating, the undissolved WC particles move to the bottom under the action of gravity. Therefore, larger and more numerous WC particles are distributed in the middle and bottom of the coating, and the newly precipitated phase and undissolved carbides are adsorbed around the WC particles. The grain refinement mechanism is shown in the figure.
[0037] Figure 4EDS surface scan results of high entropy alloy coatings with different WC particle sizes. Figure (a) shows that the elements in the coating without WC particles are evenly distributed without obvious segregation. As can be seen from Figures (b) and (c), after adding WC particles, there are incompletely melted WC particles inside the coating, and a W bonding area is formed around the WC. This phenomenon is more significant in small-sized WC particles, because the dissolution rate of small-sized WC particles during laser cladding is faster. Compared with the coating without WC particles, the degree of element segregation inside the coating increases after adding WC particles, and the segregation intensifies as the WC particle size decreases. This is mainly because the dissolution of WC particles can promote the formation of M5C carbide phase, and the new phase is mainly distributed at the grain boundary, resulting in element segregation. At the same time, smaller-sized WC particles increase the formation of carbide phase, making it easier for W and C atoms to diffuse and dissolve in the FCC main phase, further increasing the degree of element segregation.
[0038] Figure 5 The line scan element distribution diagram around different WC particle sizes shows that cracks are formed around the WC particles, and the element distribution at the cracks fluctuates significantly, which can be explained by the difference in melting and solidification temperature of the elements, which makes it easier for some elements to be enriched at the cracks. Even in the non-WC area, fluctuations in the W element are observed, indicating that new hard phases containing W and C are formed during the laser cladding process. As can be seen from the figure, a new layer of material is formed around the small-sized WC particles, which is mainly the newly generated hard phase M5C, causing a large fluctuation in the element distribution. Therefore, the smaller the WC particle size, the more drastic the element fluctuations.
[0039] Figure 6The microhardness distribution diagram of high entropy alloy coatings with different WC particle sizes. It can be seen from the figure that the hardness of the coating varies with different regions, mainly divided into the matrix area, heat-affected zone and coating area. After adding WC particles, the hardness of the coating is improved, and the hardness increase is more significant as the WC particle size decreases. This phenomenon can be attributed to the synergistic effect of three strengthening mechanisms. First, during the laser cladding process, some WC particles are decomposed into W and C atoms. These atoms dissolve into the matrix phase (FCC), aggravating the degree of lattice distortion and improving the deformation resistance of the coating, thereby increasing the microhardness and playing a role of solid solution strengthening; secondly, the dissolved W and C atoms combine with high entropy alloy atoms to form a new hard phase M5C. These hard phases are evenly distributed in the coating, hindering the slip of dislocations between grains, playing a role of dispersion strengthening, and further improving the hardness of the coating; finally, during the solidification process of the coating, WC particles act as uniform nucleation points, which increases the nucleation rate of the coating, promotes the slip between grain boundaries, enhances the deformation ability, and plays a role of fine grain strengthening. The synergistic effect of these three mechanisms leads to an increase in the hardness of the coating after adding WC particles. Compared with large-sized WC particles, the coating with small-sized WC particles has a higher hardness value, which can be explained by the fact that at the same volume fraction, the number of small-sized WC particles is larger, which increases the number of uniform nuclei inside the coating and makes the fine grain strengthening effect more significant; at the same time, small-sized WC particles are easier to melt under the action of laser, resulting in a larger number of hard phases formed inside the coating, and the solid solution strengthening and dispersion strengthening effects are more obvious, thus making the hardness value of the coating greater.
[0040] Figure 7 The friction coefficient and wear rate diagram of adding WC particles of different particle sizes. It can be seen from Figure (a) that the wear stage of the coating is mainly the running-in stage and the stable wear stage. In the running-in stage, the friction coefficient fluctuates greatly. This is mainly because when the parts are in the running-in stage, the surface will generate a large amount of friction heat, accompanied by a large amount of wear debris, so that oxides are formed on the wear surface, and some of the oxides will act as lubricants and play a lubricating role, which makes the friction coefficient of the coating fluctuate greatly. As the wear process progresses, the friction heat and the amount of wear debris generated on the coating surface tend to be stable, and the coating enters the stable wear stage. It can be seen from Figure (a) that the running-in period of the FeCoNiCrMn high entropy alloy coating is longer than that of the composite coating with added WC particles. This is mainly because after adding WC particles, the hardness of the coating is improved, the friction heat and the amount of wear debris generated during the wear process are reduced, and the undissolved WC particles generate greater resistance during the wear process, thereby reducing the running-in period of the composite coating and increasing the wear resistance of the coating. It can be seen from Figure (b) that the wear rate of the coating is reduced after adding WC particles. The wear rate change trend is negatively correlated with the hardness change trend, which is consistent with the classic Archard theory. -5 mm 3 / N·m is reduced to 7.12E-6 mm 3 / N·m, 4.68E -6 mm 3 / N·m, mainly due to the synergistic effect of the three strengthening mechanisms (solid solution strengthening, dispersion strengthening and fine grain strengthening) inside the coating after adding WC, which further enhances its wear resistance. Compared with adding large-sized WC particles, the smaller the WC size, the smaller the friction coefficient and wear rate of the coating, and the better its wear resistance. This is mainly because the smaller the WC particles, the more they melt during the laser cladding process, so that more second phases are precipitated inside the coating, and the solid solution effect is more obvious; the smaller the WC particle size, the greater the supercooling, making the internal structure of the coating more uniform; the coating with small-sized WC has a greater hardness, resulting in better wear resistance. It can be seen that as the WC particle size decreases, the wear resistance of the coating increases.
[0041] Figure 8 The SEM morphology of the wear surface of the high entropy alloy coating and the coating with different particle sizes of WC particles after friction and wear tests. Figure (a) shows the wear morphology of the FeCoNiCrMn high entropy alloy coating. It can be seen from the figure that grooves are formed on the coating surface after friction and wear, and a large number of adhesives appear around the grooves. This is a typical feature of abrasive wear and adhesive wear. The main reason for this is that the hardness of the high entropy alloy coating is relatively low. Under the combined action of the friction pair and friction force, the coating surface will produce plastic deformation, and then fall off to form abrasive particles. The abrasive particles move on the wear surface to form furrows; then, during the friction and wear process, the abrasive debris forms adhesives on the wear surface under the action of the normal force, making the wear mechanism of the coating micro-cutting abrasive wear (primary wear mechanism) and smear adhesive wear (secondary wear mechanism).
[0042] Figure (b) shows the wear surface of the coating with large-size WC particles added after friction and wear. It can be seen from the figure that a large number of furrows and adhesives appear on the coating surface after friction and wear, indicating that the wear mechanism of the coating is abrasive wear (primary wear mechanism) and adhesive wear (secondary wear mechanism). It can also be seen from the figure that after adding WC, the wear width of the coating is reduced, which can be attributed to the following reasons: First, the WC particles decompose under the action of the laser and combine with the FeCoNiCrMn high-entropy alloy atoms to form a new hard phase M5C, which hinders the occurrence of dislocations. Under the side effect of friction, the slip between the grains is reduced, thereby increasing the wear resistance of the coating; secondly, in There are incompletely dissolved WC particles inside the coating, which will generate greater resistance during the wear process. The larger the WC particles, the greater the resistance. They will break in the friction pair to form abrasive particles, which increases the abrasive wear. Secondly, WC particles will act as heterogeneous nuclei. During the solidification process, the nucleation rate inside the coating will be increased, the number of equiaxed crystals inside the coating will increase, the content of columnar crystals will decrease, and the wear resistance of the coating surface will be enhanced. Finally, W and C atoms will dissolve during the laser cladding process and be dissolved into the matrix phase (FCC), which increases the degree of lattice distortion, plays a role in solid solution strengthening, improves the coating's ability to resist deformation, and further improves the coating's wear resistance.
[0043] Figure (c) is a SEM image of the wear surface of the coating with small-size WC particles added. It can be seen from the figure that the wear morphology of the coating has changed to a certain extent, with the appearance of flaky exfoliation layers, slight furrows and a small amount of adhesion. Flaky exfoliation is a typical feature of fatigue wear. The main reason for the appearance of flaky exfoliation layers is that in the contact area, due to the repeated contact stress of the friction pair, the contact stress value exceeds the fatigue limit of the coating surface, and tiny cracks appear on the coating surface and gradually expand, eventually forming a flaky exfoliation layer, causing fatigue wear. Compared with the coating with large WC particles, as the WC particle size decreases, the wear morphology of the coating surface improves, the number of adhesions decreases, and the number and depth of furrows decrease. This can be explained as follows: first, the number of small WC particles melts more under the action of laser, more precipitation phases are generated inside the coating, and the dispersion strengthening and solid solution strengthening effects are more obvious, which improves the wear resistance of the coating; secondly, the hardness diagram shows that the smaller the WC particle size, the higher the coating hardness, which makes the coating wear more resistant; finally, the addition of small WC particles increases the number of heterogeneous nucleation inside the coating, which increases the number of equiaxed crystals on the upper part of the coating, further improving the wear resistance of the coating. It can be seen that as the WC particle size decreases, the wear resistance of the coating increases.
[0044] Fig. 9(a)-(d) are the 3D wear tracks and 2D cross-sectional wear tracks of the coating after friction and wear. As shown in Figure (a), the wear track of the high entropy alloy coating is relatively long and deep after friction and wear, and a layer of accumulation is formed near the wear track due to the extrusion of the coating by the friction pair. It can be seen that a relatively serious plastic deformation has occurred on the surface of the coating. As shown in Figures (b) and (c), after adding WC, due to the synergistic effect of precipitation strengthening, solid solution strengthening, dispersion strengthening and fine grain strengthening inside the coating, the track width and depth of the coating after friction and wear are reduced, and as the WC particle size decreases, the width and depth of the wear track are further reduced. This is mainly because the smaller the WC particle size, the more significant the synergistic effect of the strengthening mechanism, the more obvious the effect of hindering dislocation movement, and the effective inhibition of the plastic deformation of the coating. Figure (d) verifies this conclusion.
[0045] Fig.10 Polarization curves of high entropy alloy coating and coating with different WC particle sizes in 3.5% NaCl solution. Self-corrosion potential E corr It indicates the characteristics of the material's corrosion tendency. The value reflects the strength of the material's corrosion resistance. corr The larger the value, the stronger the corrosion resistance of the material, and vice versa. corr It mainly reflects the corrosion rate of the material, and its value represents the speed of the corrosion rate of the material, that is, I corr The smaller the value, the slower the corrosion rate of the material, and vice versa.
[0046] The corrosion kinetics of the coating during the electrochemical corrosion process can be analyzed from the polarization curve in the figure. The electrochemical corrosion data of the coating can be obtained by the Tafel extrapolation method, as shown in Table 3. The coating undergoes electrochemical corrosion, which can be divided into two stages: anodic reaction and cathodic reaction. When the reaction is in the anodic polarization stage, it is mainly affected by the diffusion of O atoms in the solution. As the polarization reaction proceeds, the self-corrosion potential E corr Moving toward the positive potential, the self-corrosion current density I corr Moving in the direction of decrease, when the self-corrosion current density I corrWhen the minimum value is reached, the cathode polarization reaction is separated from the anode polarization reaction, and the anode reaction enters an active dissolution state, resulting in a rapid increase in the self-corrosion current density; as the polarization reaction proceeds, the self-corrosion voltage continues to increase, and the Tafel curve separates from the polarization curve, resulting in the appearance of a passivation zone, indicating that a passivation film is formed on the coating surface. It can be seen from the figure that the three coating surfaces have formed a passivation film during the corrosion process, and it can be seen that the passivation zone is more obvious, indicating that the passivation film formed on the coating surface is stable, thereby playing a role in improving the corrosion resistance of the coating; as the corrosion voltage continues to increase, the self-corrosion current density increases instantly, indicating that the passivation film formed on the coating surface has been broken down, and pitting pits appear. As can be seen from the table, the E of the high entropy alloy coating corr = -0.863 V, I corr =-4.08E-8 A*cm 2 , the coatings after adding WC particles are E corr =-0.835 V, -0.81 V, I corr =-4.235E-8 A*cm 2 、-4.235E-8 A*cm 2 , indicating that the corrosion resistance of the coating can be improved by introducing WC particles inside the high entropy alloy coating. This situation can be explained as follows: first, after adding WC particles, a new precipitate phase M5C is generated inside the coating, and its corrosion potential is higher than that of the matrix phase (FCC), which improves the corrosion resistance of the coating; secondly, during the laser cladding process, WC particles promote the diffusion effect of active elements inside the coating, causing the active elements to move to the internal vacancies and fill the vacancies, thereby reducing the number of point defects, vacancies and dislocation density inside the coating, resulting in a decrease in the resistivity of the coating, which reduces the corrosion driving force of the coating during the electrochemical corrosion process, increases its passivation reaction in the anodic polarization reaction, and generates a more stable oxide film on the surface of the coating, thereby improving the corrosion resistance of the coating; finally, after adding WC particles, the number of heterogeneous nuclei inside the coating increases, and the degree of supercooling during the solidification of the coating structure increases, resulting in an increase in the number of equiaxed crystals inside the coating, which increases the corrosion resistance of the coating surface. Compared with adding large-sized WC particles, the smaller the WC particle size, the lower the E of the coating. corr The bigger, I corr The smaller the WC particle size, the further improved the corrosion resistance of the coating. This situation can be explained as follows: the smaller the WC particle size, the more decompositions are made under the action of laser, resulting in more precipitated phases inside the coating; the smaller the WC particle size, the more evenly distributed it is inside the coating, further promoting the diffusion of active elements and reducing the resistivity of the coating; by reducing the WC particle size, the effect of reducing the supercooling degree during the solidification of the coating structure is more obvious, thereby making the coating structure more refined and further improving the corrosion resistance of the coating surface.
[0047] Fig.11 The corrosion morphology of the coating surface after electrochemical corrosion without WC particles and with WC particles of different particle sizes. It can be seen from Figure (a) that the corrosion form of the high entropy alloy coating is mainly pitting corrosion, accompanied by intergranular corrosion. The grains fall off severely at the location of the corrosion pit, forming a honeycomb morphology. The Cr element in the FeCoNiCrMn high entropy alloy is an element with high corrosion resistance and easy passivation. During the electrochemical corrosion process, a passivation film will be formed on the coating surface, thereby isolating Cl - Ion corrosion. Pitting corrosion mainly occurs in the Cr-deficient area. Cl- ions in the corrosive solution are adsorbed on the coating surface, gradually corroding the passivation film on the coating surface, causing the passivation film to become thinner, destroying the passivation film in the Cr-deficient area on the coating surface, and promoting the loss of metal cations inside the high-entropy alloy coating, ultimately leading to the formation of irregular pitting pits on the coating surface.
[0048] Figure (b) shows the electrochemical corrosion morphology of the coating surface with the addition of large-size WC particles. It can be seen from the figure that the corrosion pits of the coating are reduced and the corrosion form is intergranular corrosion, indicating that the addition of WC particles has not changed the corrosion form of the coating. It can be explained as follows: the addition of WC particles increases the number of heterogeneous nuclei inside the coating, improves the nucleation rate inside the coating, and increases the supercooling, resulting in the transformation of coarse columnar crystals into short columnar crystals and equiaxed crystals in the coating internal structure during the solidification process, making the coating structure refined and the internal structure more uniform, which plays a role in isolating corrosion; the corrosion potential of the newly precipitated phase inside the coating is higher than that of the matrix phase (FCC), which increases the corrosion potential of the coating in electrochemical corrosion and enhances its corrosion resistance; the newly precipitated phase and WC particles reduce the unevenness and corrosion tendency of the passivation film of the coating during the corrosion process, which reduces the number of corrosion pits on the coating surface, enhances the self-healing ability of the passivation film, and reduces the occurrence of intergranular corrosion on the coating surface, further improving the corrosion resistance of the coating.
[0049] Figure (c) shows the surface corrosion morphology of the coating with small-sized WC particles added. As can be seen from the figure, by reducing the WC particle size, the corrosion pits on the coating surface are reduced and the degree of intergranular corrosion is reduced. This can be explained as follows: First, the smaller the WC particle size, the more precipitates are formed under the action of the laser. Since the corrosion potential of the precipitates is higher than that of the matrix phase and the number is larger, it is more obvious in improving the corrosion potential of the coating, thereby increasing the corrosion resistance of the coating; secondly, by reducing the WC particle size, the supercooling degree of the coating structure during solidification is further increased, so that the coating structure is further refined and the corrosion isolation effect is more obvious; finally, small-sized WC particles are more effective in reducing the unevenness of the passivation film, the corrosion tendency and the number of corrosion pits, further improving the self-healing ability of the passivation film, and further improving the corrosion resistance of the coating. The electrochemical corrosion mechanism is shown in the figure.
[0050] From the EDS of the coating surface after electrochemical corrosion, it can be seen that various elements have a certain degree of corrosion and shedding at the corrosion pit position. Among the five elements of high entropy alloy, Cr has the highest corrosion potential, which makes it have the lowest degree of corrosion and shedding during the electrochemical corrosion process. And from the figure, it can be seen that Mn has the most serious corrosion and shedding, which is mainly due to the Mn generated when the metal element undergoes an anodic reaction. 2+ Easy and Cl - After the addition of WC particles, the corrosion and shedding degree of various elements decreased. This can be explained as follows: the addition of WC particles increased the corrosion potential of the coating, enhanced the self-healing ability of the passivation film on the coating surface, and effectively isolated Cl - The penetration and shuttling of ions; and the addition of WC particles further enhances the "cocktail effect" of high-entropy alloys, which improves the corrosion resistance of high-entropy alloys and forms a more stable and dense passivation film on the coating surface during the corrosion process, which plays a corrosion inhibition role; with the decrease of WC particle size, the degree of element corrosion and shedding is further reduced, mainly because the smaller the WC particle size, the further the coating corrosion potential and the self-healing ability of the passivation film are improved, thereby slowing down the corrosion and shedding of the coating surface.
[0051] Fig.12 It can be seen that the residual stress on the surface of the high-entropy alloy coating is 476.64MPa. After adding WC particles of different particle sizes, the residual stress on the surface of the coating is increased, which is 534.42MPa and 510.46MPa respectively. This can be explained by the fact that during the laser cladding process, the instantaneous heat input is large, there is a large temperature gradient between the coating and the substrate, and the expansion and contraction between the components of the molten pool are uneven, which makes the coating have a large residual stress inside, and with the coverage of the cladding layer, the heat input continues to increase, resulting in greater thermal deformation, so that there is a large residual stress on the surface of the coating after cooling; when WC particles are added inside the coating, the residual stress on the coating surface increases, which can be explained by the existence of a certain thermal expansion coefficient between the high-entropy alloy particles and the WC particles. With the increase of heat input, the thermal expansion and contraction between the two are inconsistent, which makes stress concentration points appear inside the coating, resulting in an increase in internal residual stress; and it can be seen from the figure that when the WC particle size is larger, the residual stress on the coating surface is greater, mainly because the larger the WC particles, the greater the difference in thermal expansion coefficient between the WC particles and the high-entropy alloy particles, resulting in more obvious stress concentration inside the coating, resulting in a larger residual stress value on the coating surface.
[0052] Table 3 Corrosion potential (Ecorr) and corrosion current density (Icorr) of different coatings FeCoNiCrMn Bigger size WC Smaller size WC <![CDATA[E corr (V)]]> -0.863 -0.835 -0.81 <![CDATA[I corr (A*cm 2 )]]> -4.08E-8 -4.235E-8 -4.376E-8 In summary, by adding 15% by mass of WC particles in Example 1-2 of the present invention, the comprehensive mechanical properties of the high entropy alloy composite coating prepared are improved compared with the control example. At the same time, experiments show that the strengthening effect is maximum when the particle size of the added WC particles is in the range of 20 μm to 55 μm.
[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technology in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes, characterized in that: The alloy coating is composed of FeCoNiCrMn high entropy alloy powder and WC particles, the mass fraction of the FeCoNiCrMn high entropy alloy powder is 85%, the mass fraction of the WC particles is 15%, and the particle size of the WC particles is 20μm~55μm or 100μm~150μm.
2. A FeCoNiCrMn high entropy alloy coating reinforced with different WC grain sizes according to claim 1, characterized in that: The molar fractions of the elements in the FeCoNiCrMn high entropy alloy powder are as follows: the molar fraction of Fe is 18-22%, the molar fraction of Co is 18-22%, the molar fraction of Ni is 18-22%, the molar fraction of Cr is 18-22%, and the molar fraction of Mn is 18-22%.
3. A FeCoNiCrMn high entropy alloy coating reinforced with different WC grain sizes according to claim 1, characterized in that: The particle size of the WC particles is 20 μm to 55 μm.
4. A method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes as claimed in claim 1, characterized in that: Specifically include the following steps: Step 1, ball-milling the FeCoNiCrMn high entropy alloy powder and the WC particles to obtain a mixed powder; Step 2: Put the mixed powder into a beaker and place it in a drying oven for drying; Step 3, pre-treating the substrate surface; Step 4: The powder is passed through a synchronous powder feeding laser cladding device to obtain a WC particle reinforced FeCoNiCrMn high entropy alloy coating.
5. The method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes according to claim 4, characterized in that: In step 1, the mass percentage of the ball-milled mixed ceramic balls and the FeCoNiCrMn high entropy alloy powder is 1:1, the rotation speed of the ball mill is 200-500 rpm, and the mixing time of the mixed powder is 12-24 hours.
6. The method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes according to claim 4, characterized in that: In step 2, the operating temperature of the drying oven is 120-150° C., and the time is 8-12 hours.
7. The method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes according to claim 4, characterized in that: In step 3, the substrate is pretreated by first grinding off the oxide film on the surface of the alloy with sandpaper, then spraying the surface with sandblasting to remove oil stains, then cleaning with alcohol, and finally drying with a hair dryer.
8. The method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes according to claim 4, characterized in that: In step 4, the laser cladding process parameters for preparing the composite coating are: laser power of 1200W~1800W, scanning speed of 600mm / min~720 mm / min, spot diameter of 6 mm, powder feeding amount of 0.6g / min~10 g / min, defocusing amount of 36 mm, and coating overlap rate of 45%.
9. The method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes according to claim 4, characterized in that: In step 4, the layer thickness of the high entropy alloy coating is 0.4-0.8 mm.
10. The method for preparing a FeCoNiCrMn high entropy alloy coating reinforced with different WC particle sizes according to any one of claims 4 to 9, characterized in that: The particle size of the FeCoNiCrMn high entropy alloy powder is 45-105 μm.